Komunikasi Visual Kartun Sompret Karya I Wayan Sadha - Nuriarta, I Wayan; Indram Bayu Artha, I Gede Agus; Pramesti, Ni Putu Dhea; Sastra Wibawa, Pande Putu (Widya Duta: Jurnal Ilmiah Ilmu Agama dan Ilmu Sosial Budaya, 2021)
This paper was written to read visual signs and verbal marks contained in the cartoon Sompret by I Wayan Sadha. I Wayan Sadha's Sompret cartoon has its uniqueness as a work of visual communication. The uniqueness is that the visual communication of this cartoon presents illustrations, typography, and layouts with a deep appreciation of Balinese culture. The illustration presents a Balinese wearing a headdress is a representation of a Balinese in traditional culture. The illustration of a Balinese without a headdress is a representation of a Balinese who is in the modern culture. The typography used utilizes the display font to present the conversation and clarify the description of the image. The letters are used to explain the issue raised as Sadha's opinion and point of view on the Bali issues. Sadha's Sompret Cartoons only use lines, no color, so his works appeared as black and white cartoons. Sompret cartoons used the symmetrical balance composition and hidden balance layout, the perspective of human eye level, and the perspective of a bird's eye. This research uses descriptive qualitative research method. Semiotic theory is used in this research and focus on denotation and connotation meaning. Denotationally, the Sompret cartoon of Sadha presents a narrative of events based on the issue raised related to Balinese traditional culture and the flow of globalization. The work is created in a one-panel cartoon. The story of this cartoon sometimes with conversations of several characters or only illustrations of the characters without any conversation. With the narrative being built, the meaning of the connotation can be read. The connotations meaning of Sompret cartoons as opinion cartoons is showing the flow of globalization or modern culture in the middle of the strength of the Balinese traditional culture. Connotatively this cartoon can be read as a development of globalization in Bali.